Reinterpreting Female Sexuality in Islam: A Maqāṣidī Exegesis of QS Āli ‘Imrān:14 toward Gender-Just Hermeneutics - Sarwanih (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
This study analyzes the issue of female sexuality in Islam through a maqāṣidī exegesis of QS Āli ʿImrān verse 14. Sexuality, often interpreted through patriarchal and biased lenses, poses a significant challenge to developing a gender-just Islamic perspective. This research employs a library-based method, drawing from classical and contemporary tafsir works as well as scholarly literature on sexuality in Islam. The findings indicate that conventional interpretations frequently portray women as sources of temptation (fitnah). In contrast, the maqāṣidī approach understands the verse as a universal reminder of worldly attractions for all human beings. Sexual desire is viewed as a divine slot deposit 5000 gift that supports family formation, preserves human dignity (ḥifẓ al-ʿirḍ), life (ḥifẓ al-nafs), and intellect (ḥifẓ al-ʿaql). This study emphasizes the equal moral responsibility of men and women and the need to develop a more inclusive and humanistic tafsir methodology. The findings aim to contribute to the advancement of gender-sensitive hermeneutics in contemporary Qur'anic studies.